"I Should not Forget the Apples!"—Mind‐Wandering Episodes Used as Opportunities for Rehearsal in an Interrupted Recall Paradigm. Issue 4 (24th April 2017) - Steindorf, Lena; Rummel, Jan
Summary: Mind‐wandering is mostly studied for its negative effects on ongoing cognitive tasks but may be also of adaptive value. We tested the idea of mind‐wandering providing opportunities for rehearsal by asking participants to study 20 grocery items for a recall test. After cued recall of 10 items, participants were either told that the recall task was finished or that it was interrupted for another task. All participants then performed a two‐back task during which thought contents were repeatedly probed. Cued recall of the remaining items was better in the interrupted than in the finished condition, and this effect was accompanied by a more efficient rehearsal strategy: Participants' thought‐reports in the interrupted condition revealed a stronger and more persistent engagement in shopping‐task‐related thoughts. Activating a relevant goal led to mind‐wandering episodes being persistently used as opportunities for rehearsal revealing participants' adaptive usage of off‐task thoughts.Copyright © 2017 John Wiley & Sons, Ltd.